Psychological Factors of EFL Students on Speaking Performance - Hafis, Maliqul; Widya, Retno (STKIP Yapis Dompu, 2021)
This research aimed to explore the psychological factors that caused college learners felt hard in delivering speaking performance. This study was conducted to the fifth semester English program students at IKIP PGRI Pontianak. The 37 students were chosen as the participant of this study which was obtained by doing purposive sampling. It was chosen since the problem occurred in IKIP PGRI Pontianak specifically at the fifth semester students. The research design used in this research was descriptive qualitative and quantitative design. The data were taken from online questionnaire and semi structured interview of students. The questionnaire was employed to find out the dominant factor. The other tool of collecting data was students’ semi structured-interview. It was used to support the questionnaire data. The researcher revealed that the psychological factor including anxiety, shyness, lack of confident, lack of motivation, and fear of making mistake were some factors that influenced students’ speaking performance. The researcher investigated that between five aspects, the dominanat factors influenced the students’ speaking performance was anxiety with the mean score (2,06). They worried to do speaking performance. Another factor were shyness, lack of confident, lack of motivation, and fear of making mistake, those factors hindered learners to practice their speaking ability in front of the class. The conclusions of this research were students feel anxious and afraid of making a mistake when they did speaking performance. This study suggested that the lecture should aware those factors affected students’ speaking performance in the class.